Upaya Peningkatan Pengetahuan Remaja terhadap Kesehatan Mental di SMPIT Nurul Ilmi Kota Jambi - Muhammad Hidayat; Hesty Hesty; Maimaznah Maimaznah; Iin Indrawati; Mila Triana Sari; Vevi Suryenti Putri (Jurnal Abdimas Kesehatan (JAK), 2026)
Emotional development during adolescence typically involves high energy and intense emotions, while self-control is not yet perfect. Uncontrolled changes and challenges that occur during adolescence can trigger mental and emotional problems. Similarly, a lack of knowledge about mental health among adolescents at SMP IT Nurul Ilmi in Jambi City can negatively impact the surrounding community. The community service team can provide health education to adolescents. Education is provided in the form of lectures and discussions using leaflets. Ten students participated in this activity. Evaluation was conducted through pretests and posttests. The results of this community service activity showed an increase in student knowledge from 20% to 100%. Education also increased student awareness of the importance of correctly applying mental health principles. This activity demonstrates that education is effective in increasing adolescent knowledge about mental health at SMP IT Nurul Ilmi in Jambi City.